Effectiveness of Community Service as Sanction in the Jordanian Penal Code - Almomani, Hala Fayiz; Rajamanikam, Ramalinggam; Said, Muhamad Helmi Md. (Journal of Posthumanism, 2025)
This article presents a comprehensive analysis of the provisions of the penalty of community service in the Jordanian Penal Code, shedding light on its effectiveness as an alternative to imprisonment. Utilizing a legal analysis approach coupled with an extensive review of pertinent literature and real-world case studies, deeper insights into the impact of community service penalties in Jordan can be gained. The findings of the article provides compelling evidence that community service penalties yield a significantly lower rate of recidivism when compared to traditional imprisonment. This shows the potential of community service as a powerful rehabilitative tool within the Jordanian legal system. Focusing on specific regions of Jordan over the past decade, the article offers a nuanced understanding of the practical application of community service penalties. Importantly, these findings hold significant implications for the Jordanian legal framework. By encouraging the broader adoption of community service penalties, policymakers can anticipate a decrease in recidivism rates and an enhancement in rehabilitation outcomes. This aligns with the overarching goal of the Jordanian legislature, which aims to empower judges with the discretion to replace imprisonment sentences with alternative punishments. In doing so, the legal system can harmoniously achieve both punitive and rehabilitative objectives, ultimately contributing to a more just and effective criminal justice system in Jordan.